FORMATION OF RESEARCH COMPETENCIES IN THE PROCESS OF TRAINING PENITENTIARY PSYCHOLOGISTS - Slobodskaya, Irina; Filipova, Elena; Martynyuk, Oxana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Training of penitentiary psychologists on the educational program «Psychology of official activity» is conducted in two universities of the Federal penitentiary service (FSIN of Russia). An important component of the practical and scientific activities of the penitentiary psychologist is the development, conduct and analysis of various psychological studies that require a high level of development of the necessary competencies. This article discusses the author's methodology IVDRC (Individual vector of development of research competencies), used in the training of penitentiary psychologists in the study of mathematical methods in psychology. The methodology is based on the continuity and professional orientation of training courses, individual approach, support and control of the stages of study of disciplines, the use of information technologies, own methodological materials and manuals. The developed technique is a generalization of long-term experience of teaching mathematical disciplines in departmental higher education institution. The technique of IVDRC has been successfully used for several years at the psychological faculty of the Vologda Institute of Law and Economics of the Federal Penal Service of Russia. To date, more than 150 cadets have been trained using the technology of IVDRC. The article analyzes some results and efficiency of its application using statistical methods.